Isolation, Identification and Quantification of Essential Oils in Cyprus and Anatolia Thyme - Khaleal, Wihad Mohamed Hussain (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
In this study our aim was to extract, identify and quantify the essential oils in locally obtained thyme samples grown in Cyprus and Anatolia. The samples comprised three Cypriot specimens, one of which grew wild and two of which were grown commercially; and two commercially grown Anatolian samples. All the specimens were obtained as the dry herb. The essential oils from these were isolated by hydrodistillation using a Clevenger type Apparatus. Analyses were carried out by Gas Chromatography-Mass Spectrometry. In the extracts, up to 45 different constituents could be identified which accounted for about 95% of the total essential oils extracted. The major constituents in all the samples were found to be carvacrol (about 90 % of the total) and p-cymene (around 3 %). We can therefore predict the chemotype of our five samples as carvacrol but exactly which species they are requires further botanical identification. The higher yields of essential oils were obtained from the Cyprus specimens, the highest being from the wild Cyprus thyme. Keywords: Carvacrol, Clevenger-type Apparatus, essential oils, Gas Chromatography- Mass Spectrometry, Thyme.

ÖZ; Bu çalışmanın amacı Kıbrıs ve Anadolu‟da yetişen ve yerel olarak temin edilen bazı kekik örneklerindeki uçucu yağların damıtma yoluyla elde edilmeleri ve içeriklerinin ne olduğunu ve her bir maddeden ne kadar olduğunu tespit etmektir. Çalışılan örneklerin üçü Kıbrıs‟ta, ikisi ise Anadolu‟da yetişmiştir. Temin edilen tüm örnekler kurutulmuş haldeydi. Uçucu yağlar Clevenger tipi bir sulu-damıtma düzeneği ile damıtılarak elde edildi. Analizler Gaz Kromatografi – Kütle Spektroskopisi ile gerçekleştirildi. Elde edilen uçucu yağlarda toplamın yüzde 95‟ini oluşturan 45 farklı madde tanımlandı. Tüm örneklerde, uçucu yağın çoğunluğunu oluşturan madde karvakrol (takriben 90 %) olarak tespit edilirken ikinci sıradaki madde p-cymene (takriben 3 %) oldu. Bu sonuçlara göre beş örneğimizin kimotipinin karvakrol olarak tanımlanması gerekeceğini düşünüyoruz. Ancak nihai isimlendirme örneklerimizin öncelikle botanik olarak tür ve cinsinin tanımlanması ile mümkün olacaktır. En çok uçucu yağ miktarı Kıbrıs kekik örneklerinden elde edilmiştir. Anahtar Kelimeler: Karvakrol, Clevenger-tipi cihaz, uçucu yağlar, Gaz Kromatografi-Kütle Spektroskopisi, Kekik.
Master of Science in Chemistry. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2015. Co-Supervisor: Assist. Prof. Dr. Aybike Yektaoğlu, Supervisor: Assist. Prof. Dr. Mehmet Garip.
Keywords: Chemistry; Essential Oils - Herbs - Thyme - Chemistry; Thyeme - Cyprus - Turkey - Anatolia; Carvacrol; Clevenger-type Apparatus; essential oils; Gas Chromatography - Mass Spectrometry; Thyme